Implementation Of QCA Logic Gates For The Design Of An ALU Based On QCA (International Journal of Environmental Sciences, 2025)
In this paper, we present the design and imple- mentation of a basic Arithmetic Logic Unit (ALU) cell using Quantum-dot Cellular Automata (QCA) technology. Our focus is on enhancing the training process of Long Short-Term Memory (LSTM) algorithms by accelerating data transfer rates, especially in Multiply-Accumulate (MAC) operations. While the complete QCA-based ALU design is a future goal, we have successfully implemented and tested a crucial component—the Quantum-dot based inverter cell. Initial simulations using the QCA tool have shown a significant performance boost, validating the potential of this technology for acceleration. Right now, the entire ALU that makes use of a quantum computing circuit is just a concept. The QCA inverter circuit and logic gates offer a strong basis because they are 90% equivalent to the traditional MOSFET inverter. It has been verified that it can scale its ALU.This foundation will be expanded upon in our future work to create the complete ALU architecture, which offers a viable means of effectively accelerating computation.